Effects of cross section size and transverse rebar on the behavior of short squared RC columns under axial compression. (1st July 2017) - Jin, Liu; Du, Min; Li, Dong; Du, Xiuli; Xu, Haibin
Highlights: Failure of 26 geometrically similar RC columns under axial compressive loading are reported. The cross-sectional width of the tested columns ranges from 267 mm to 600 mm. The nominal strength of RC columns follows closely the size effect law proposed by Bažant. A meso-scale method for the simulation of size effect of RC members is developed. Abstract: The paper reports the results of a series of tests of geometrically similar stocky reinforced concrete (RC) columns having different sizes with a ratio of 1:1.5:2.25. The effects of stirrup ratio, tie arrangement type and yield strength of stirrups on the failure and size effect of RC columns under axial compression were explored. Moreover, a 3D meso-scale numerical method for the simulation of failure of RC members was developed. The test observations demonstrate the existence of size effect in larger-sized RC columns, and the failure is governed by fracture. With increasing the stirrup ratio, the number of stirrups leg and yield strength of stirrups could make the enhancement of nominal strength and improvement of ductility capacity of RC columns. The RC columns with a lower stirrups ratio, a smaller number of tie legs, and a lower yield strength of stirrups present much more brittle failure, exhibiting much stronger size effect. The test data illustrates that the nominal compressive strengths are consistent with the size effect law (SEL) proposed by Bažant. Moreover, good agreements between the simulation results and the test observations illustrate the reasonability of the developed meso-scale simulation approach.